AN EMPIRICAL STUDY ON THE IMPACT OF PERSONALITY TRAITS ON SOCIAL SPORTS MARKETING (Isagoge - Journal of Humanities and Social Sciences, 2023)
In the study, the impact of personality traits on social marketing of sport was investigated.  A total of 401 students who continue their education and training in different departments voluntarily participated in the study. The e-survey method prepared in the internet environment was applied as a data collection technique in the research.  Two scales were used in the application. The personality scale developed by(Benet-Martínez & John, 1998). and adapted into Turkish by (Sümer & Sümer, 2005). was used.  Secondly, the “Attitude Scale on Social Marketing of Sports” developed by (Ünal, 2009). was used in the study. There is a high level of positive relationship between satisfaction. However, this relationship is not statistically significant (R: ,074 , R2: ,006 ,   p < 0,05).  According to the results of the T- test on the significance of the regression coefficient, it is seen that personality traits do not have a significant effect (T ፦1,486, p < 0.05).   Examining the impact of personality characteristics in the social aspect of this type of marketing, which targets large audiences such as sports marketing, especially for companies involved in this sector and, of course, is great for clubs is of great importance. Because, companies should pay attention to this detail in their next strategic moves in this area. Future studies can be applied on businesses. Different dimensions of personality traits can be considered. Social sports marketing can be evaluated in the context of product mix. And this evaluation can be constructed both in terms of consumers (fans). and businesses.
Keywords: Sports marketing; Physical Activity; Personality; Sports; Society